Tinjauan Literatur Tentang Manfaat Permainan Tradisional Awuta untuk Anak Usia Dini - Rasqah Maghfiratunnisa; Nadiva Adelia Akilie; Nabila Sinto; Jaliha Kadir; Nurul Fajrun Dadu; Dwiva Muzdalifah Daud; Mita Sari (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
Traditional games play an important role in early childhood development, particularly in stimulating creativity and social skills. One such game from Gorontalo, Indonesia is Awuta, which is now rarely played but holds great potential in supporting children's growth. Awuta enhances fine and gross motor skills, encourages strategic thinking, and fosters teamwork. The game also incorporates cultural and philosophical values about the cycle of life and death. This study uses a qualitative literature approach to explore how Awuta supports cognitive, social, and physical development while strengthening cultural identity. Reviving traditional games like Awuta is crucial for balanced learning and character education in the digital era.